“It’s Our Country”: First Nations’ Participation in the Indian Pavilion at Expo 67 - Rutherdale, Myra; Miller, Jim (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2006)
AbstractThis paper traces the history of Aboriginal people’s participation in national spectacle and argues that the Indian Pavilion at Expo 67 was unique in its assertion of the portrayal of Native/Newcomer relations. Historians have interpreted the impact of the Indian Pavilion as an event that awakened non-Native Canadians to both the plight of Aboriginal peoples and their increasing unwillingness to suffer in silence. The controversy over the contents and general argument of the Indian Pavilion followed soon after the release of the two-volume Hawthorn Report on the social and economic conditions First Nations faced, and operated just as the federal government was initiating a series of talks with First Nations leaders to forge a new policy towards First Nations. At the same time, there is little evidence that the Indian Pavilion, whatever succès de scandale it enjoyed, had a lasting impact on public opinion or policymakers. Where the experience of mounting, operating, and defending the Indian Pavilion did matter, however, was with First Nations themselves. Whether causation or coincidence, the newfound confidence and pride that underlay the creation of the Indian Pavilion was completely consistent with the positive demeanour of Aboriginal political leaders from the late 1960s on.